Analysis of the Effect of School Environment and Compensation on Performance of Vocational School Teachers - Dila Erlianti; Mumu Muzayyin Maq; Tri Endar Susianto; Ismail Nasar; Apit Fathurohman (Departement of Mathematics Education, 2023)
This study's objective was to determine and evaluate the impact of compensation and the workplace on teachers' performance in private schools, involving 70 teachers. The survey method is used in this study. A questionnaire technique was used to collect data. Path analysis was used to examine the data. The study's findings indicate that there is a direct relationship between pay and teacher performance with a Sig. 0.00 < 0.05, a direct relationship between the work environment and teacher performance with a Sig. 0.00 < 0.05, and a direct relationship between pay and the work environment. The study's conclusion is that the increase in teacher performance is determined by the compensation provided by the school and an adequate work environment.